2021
DOI: 10.1002/ijgo.13838
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose aspirin improves blood perfusion of endometrium of unexplained recurrent biochemical pregnancy loss

Abstract: Due to the advent of high-sensitivity pregnancy tests, biochemical pregnancy losses (BPLs) have been found to be much more common than previously thought, involving as many as 50%-60% of all pregnancies. 1 This is because most women who experience a BPL never even realize they are pregnant unless they are trying to conceive and are testing regularly and early. Unlike clinical early miscarriage, in which karyotypically abnormal embryos are the cause of 50% of losses, 2 the exact causes of BPL remain unknown. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, PTE (10 mg kg −1 )-treated mice were the most effective in suppressing the development of experiment AAAs, which was consistent with the dose of aspirin used in the clinic. In previous studies, 58–60 a high dose of aspirin had a poorer effect than a low dose of aspirin, which may increase the risk of bleeding. In addition, when the concentration of PTE increases, some toxic side effects may occur in mice.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, PTE (10 mg kg −1 )-treated mice were the most effective in suppressing the development of experiment AAAs, which was consistent with the dose of aspirin used in the clinic. In previous studies, 58–60 a high dose of aspirin had a poorer effect than a low dose of aspirin, which may increase the risk of bleeding. In addition, when the concentration of PTE increases, some toxic side effects may occur in mice.…”
Section: Discussionmentioning
confidence: 91%
“…Some studies also reveal that BPL is linked to female age, embryonic development stage, or abnormal chromosome structure. However, more and more studies describe that BPL is not related to female age [20,21], endometrial abnormality [22,23], or chromosome structure abnormality [21,23]; instead, poor embryo quality dose increases BPLR [24]. Few studies have reported the increase in BPL caused by male factors.…”
Section: Discussionmentioning
confidence: 99%
“…Late miscarriage occurs after 12 gestational weeks. Unlike early miscarriage, most studies conclude that the leading causes of BPL are endometrial factors rather than embryonic factors [ 1 6 ]. On the contrary, more than 50% causes of early miscarriage are abnormal embryo karyotypes.…”
Section: Introductionmentioning
confidence: 99%